(untitled) (Vietnam Journal of Community Medicine, 2026)
Background: Ventilator-associated pneumonia (VAP) is a common complication in patients with traumatic brain injury (TBI), contributing to increased treatment burden. Endotracheal suctioning is an essential procedure but may induce physiological disturbances and increase infection risk if not properly performed. Closed suction systems are expected to mitigate these disadvantages. Objective: To evaluate the effectiveness of VAP prevention, adverse effects, and economic efficiency of the closed suction system in mechanically ventilated TBI patients. Methods: A prospective, controlled interventional study was conducted on 101 TBI patients requiring mechanical ventilation for ≥48 hours. Patients were divided into two groups: closed suction (n=52) and open suction (n=49). Outcome measures included VAP incidence and onset timing, clinical progression, changes in SpO₂, suction-related complications, and economic efficiency. Results: The closed suction group showed a significantly lower VAP incidence compared to the open suction group (34.6% vs. 55.1%; p<0.05) and a delayed onset of pneumonia. During suctioning, SpO₂ remained more stable and the incidence of atelectasis was significantly reduced in the closed suction group. No significant differences were observed between groups regarding causative pathogens, duration of mechanical ventilation, or ICU length of stay. The daily suction-related cost per ventilated patient was lower in the closed suction group. Conclusion: The closed suction system is effective in preventing VAP, minimizing physiological disturbances during suctioning, and providing economic benefits in mechanically ventilated TBI patients. This method should be prioritized in critical care practice.